An Outline of Elementary Accounting / Accounting Problems With Answers (Book). - Cannon, Arthur M.; Moss, Morton F. (The Accounting Review, 1953)
Reviews two books. "An Outline of Elementary Accounting," 3rd ed., by Royal D. M. Bauer and Paul H. Darby; "Accounting Problems With Answers," by Joseph C. Schabacker and Paul K. Schroeder